The Influence of Environmental, Social, and Governance (ESG) Disclosure and Good Corporate Governance on Firm Value with Corporate Reputation as an Intervening Variable in Companies Listed in the IDXESGL Stock Index for the Period 2018-2022 - Ufaira, Raqiqah; Yusra, Irdha (Devitara Innovations, 2024)
The aim of this research is to analyze the effect of environmental, social and governance (ESG) disclosure and good corporate governance on company value by using company reputation as an intervening variable in companies listed on the IDXESGL stock index. The period is from 2018 to 2022. This research uses a quantitative approach. This research covers companies that are members of the IDXESGL stock index from 2018 to 2022. A total of 30 companies and a total of 135 observations were used as samples. Data were analyzed using regression analysis and hypothesis testing was carried out using the t test using SPSS version 25 software. The findings show that ESG does not have a significant impact on corporate reputation. The board of directors also does not have a significant effect on the company's reputation. However, ESG has been proven to have a positive and significant impact on company value. On the other hand, the board of directors does not have a significant influence on company value. Furthermore, this research concludes that reputation does not act as a mediator in the relationship between ESG and shareholder value. However, reputation can mediate the relationship between board of directors and firm value.